Association of severe intrahepatic cholestasis of pregnancy with adverse pregnancy outcomes: a prospective population-based case-control study - Geenes, V; Chappell, L; Seed, P; Steer, P; Knight, M; Williamson, C (Wiley, 2014)
Intrahepatic cholestasis of pregnancy (ICP) is a pregnancy-specific liver disease, characterized by maternal pruritus and raised serum bile acids. Our objectives were to describe the epidemiology and pregnancy complications associated with severe ICP and to test the hypothesis that adverse perinatal outcomes are increased in these women. A prospective population-based case-control study with national coverage was undertaken using the UK Obstetric Surveillance System (UKOSS). Control data for comparison were obtained from women with healthy pregnancy outcome through UKOSS (n = 2,232), St Mary's Maternity Information System (n = 554,319), and Office for National Statistics (n = 668,195). The main outcome measures investigated were preterm delivery, stillbirth, and neonatal unit admission. In all, 713 confirmed cases of severe ICP were identified, giving an estimated incidence of 9.2 per 10,000 maternities. Women with severe ICP and a singleton pregnancy (n = 669) had increased risks of preterm delivery (164/664; 25% versus 144/2200; 6.5%; adjusted odds ratio [OR] 5.39, 95% confidence interval [CI] 4.17 to 6.98), neonatal unit admission (80/654; 12% versus 123/2192; 5.6%; adjusted OR 2.68, 95% CI 1.97 to 3.65), and stillbirth (10/664; 1.5% versus 11/2205; 0.5%; adjusted OR 2.58, 95% CI 1.03 to 6.49) compared to controls. Seven of 10 stillbirths in ICP cases were associated with coexisting pregnancy complications. These differences remained significant against national data. Risks of preterm delivery, meconium-stained amniotic fluid, and stillbirth rose with increasing maternal serum bile acid concentrations.In the largest prospective cohort study in severe ICP to date, we demonstrate significant increased risks of adverse perinatal outcomes, including stillbirth. Our findings support the case for close antenatal monitoring of pregnancies affected by severe ICP.